Graphene and preparation method thereof, graphene conductive slurry, electrode plate, lithium ion battery and electric equipment
By controlling the thickness and particle size of graphene, forming a layer overlap support structure, and preparing through plasma-enhanced chemical vapor deposition reaction, the problems of graphene prone to agglomeration and poor conductivity in lithium-ion batteries are solved, and the high rate performance and good cycle stability of the battery are achieved.
Patent Information
- Application Number
- CN202311134123.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-31
- Publication Date
- 2025-02-28
Smart Images

Figure CN119528130A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of graphene preparation, and in particular to graphene and a preparation method thereof, a graphene conductive slurry, an electrode sheet, a lithium ion battery and electrical equipment. Background Art
[0002] Two-dimensional graphene materials are used in lithium-ion batteries because they can construct an efficient conductive network of point-surface structures. However, two-dimensional graphene is prone to agglomeration during the dispersion process, and agglomerated graphene will also hinder the transmission of lithium ions to a certain extent, affecting its performance in lithium batteries.
[0003] In the prior art, graphene oxide is prepared by a modified Hummers method, and graphene is obtained by chemical reduction or thermal reduction. The graphene prepared by this method has a large number of negatively charged oxygen-containing functional groups on its surface, and the repulsive force between the negative charges inhibits the aggregation of graphene. However, the presence of a large number of oxygen-containing functional groups will affect the conductivity of graphene, and thus affect the battery rate performance.
[0004] Therefore, it is very necessary to provide a graphene with good dispersibility and low agglomeration. Summary of the invention
[0005] The purpose of the present invention is to overcome the problems of easy agglomeration and poor conductivity of graphene in the prior art dispersion process, and to provide a graphene and a preparation method thereof, a graphene conductive slurry, an electrode plate, a lithium ion battery and an electrical device.
[0006] In order to achieve the above-mentioned purpose, the first aspect of the present invention provides a graphene, wherein the thickness of the graphene sheet is 2-6nm, the diameter of the graphene sheet is 0.2-1μm; and the oil absorption value of the graphene is 300-800mL / 100g.
[0007] A second aspect of the present invention provides a method for preparing graphene, comprising:
[0008] (1) Under the action of an auxiliary gas, a carbon source gas and an inorganic salt are subjected to a plasma enhanced chemical vapor deposition reaction to obtain a salt-encapsulated graphene product;
[0009] (2) washing the salt-encapsulated graphene product and subjecting it to ultrasonic cavitation treatment to obtain graphene;
[0010] The thickness of the graphene sheet is 2-6 nm, the diameter of the graphene sheet is 0.2-1 μm, and the oil absorption value of the graphene is 300-800 mL / 100 g.
[0011] A third aspect of the present invention provides graphene obtained by the preparation method.
[0012] A fourth aspect of the present invention provides a graphene conductive slurry, wherein the slurry includes the graphene.
[0013] A fifth aspect of the present invention provides an electrode plate, wherein the electrode plate is prepared from the graphene conductive slurry.
[0014] A sixth aspect of the present invention provides a lithium-ion battery, wherein the lithium-ion battery comprises the graphene conductive slurry.
[0015] A seventh aspect of the present invention provides an electrical device, wherein the electrical device comprises the multiple lithium-ion battery.
[0016] Through the above technical scheme, the present invention controls the thickness and particle size of graphene within a certain range, ensures that the graphene has a certain rigidity, makes the graphene structure more stable, and reduces the agglomeration between graphene layers. When the graphene is used in the pole piece of a lithium-ion battery, the graphene is perpendicular to the pole piece, and while constructing a longitudinal conductive network, it minimizes the obstruction to the diffusion of ions in the direction perpendicular to the pole piece; the oil absorption value of the graphene is 300-800mL / 100g, and dispersing the graphene between the electrode active materials is also beneficial to the storage of the electrolyte, so that lithium ions can migrate to the surface of the electroactive material nearby, reducing the ion migration resistance. Therefore, when the graphene is used in the pole piece of a lithium-ion battery, the chemical activity of the pole piece can be improved in both directions from electronic conduction and ion migration, thereby ensuring that the lithium-ion battery has a better rate performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 is a scanning electron microscope image of Example 1;
[0018] Figure 2 is the thermogravimetric spectrum of Example 5;
[0019] Figure 3 This is the XPS spectrum of Example 7. DETAILED DESCRIPTION
[0020] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0021] A first aspect of the present invention provides graphene, wherein the graphene sheet thickness is 2-6 nm, the graphene sheet diameter is 0.2-1 μm, and the graphene oil absorption value is 300-800 mL / 100 g.
[0022] In the present invention, the sheet diameter is the average sheet diameter, which can be measured by SEM. The graphene has a sheet-layer overlapping support structure, such as Figure 1 As shown, due to the formation of such a supporting structure, the agglomeration problem between graphene layers caused by π-π stacking is alleviated.
[0023] In the present invention, the graphene has a lamellae overlap support structure, which can prevent the stacking of graphene lamellae due to π-π self-assembly, and is conducive to its uniform dispersion; at the same time, by controlling the lamellae thickness of the above-mentioned graphene to be 2-6nm and the lamella diameter to be 0.2-1μm, it is ensured that the graphene material has a certain rigidity, so that the above-mentioned support structure is well maintained, and the agglomeration between the graphene layers is further reduced. When this graphene is used for the pole piece of a lithium-ion battery, the graphene is perpendicular to the pole piece, and the longitudinal conductive network is constructed while minimizing the obstruction to the diffusion of ions in the direction perpendicular to the pole piece; in addition, the oil absorption value of the above-mentioned graphene is 300-800mL / 100g, and it is dispersed between the electrode active materials, which is conducive to the storage of the electrolyte, so that lithium ions can migrate to the surface of the electroactive material nearby, and reduce the ion migration resistance. Therefore, adding the above-mentioned graphene can improve the chemical activity of the pole piece in both electronic conduction and ion migration, thereby ensuring that the lithium-ion battery has a better rate performance.
[0024] In some specific embodiments of the present invention, the graphene sheet diameter is 0.5-0.85 μm. Graphene with a particle size within this range has stronger rigidity and a more stable sheet layer overlap support structure.
[0025] In some specific embodiments of the present invention, the oil absorption value of the graphene is preferably 500-800 mL / 100 g. This value is much higher than that of existing graphene materials. High oil absorption value is beneficial to the ion diffusion process between electrode active materials, thereby reducing the internal resistance of the battery. The oil absorption value is determined by referring to the carbon black oil absorption value test method.
[0026] In some specific embodiments of the present invention, the carbon content of the graphene is ≥98wt%, preferably ≥99wt%. The graphene within this range has stronger conductivity.
[0027] In some specific embodiments of the present invention, the graphene further contains a doping element A, and the doping element A is selected from sulfur and / or nitrogen. Doping element A in graphene can improve the electron cloud distribution in the graphene carbon layer, improve the conductivity and ion wettability of the graphene interface, and thus reduce the impedance of the battery.
[0028] In some specific embodiments of the present invention, the doping element A contained in the graphene forms an AC bond with the carbon element in the graphene sheet. Due to the different electronegativity between the doping element A and the carbon element, the induction effect between the AC bonds improves the electron cloud distribution on the graphene surface, enhances the conductivity and ion wettability of the graphene interface, thereby reducing the impedance of the battery and increasing the rate performance.
[0029] In some specific embodiments of the present invention, the doping element A contained in the graphene is embedded in the carbon lattice, replacing the carbon atoms at the original sites and forming bonds with multiple surrounding carbon atoms, which has a stronger induction effect, further improves the electron cloud distribution, enhances the conductivity and ion wettability of the graphene interface, thereby reducing the impedance of the battery and increasing the rate performance.
[0030] Graphene is a supramolecular structure formed by a qualitative arrangement of six-membered rings composed of carbon atoms. The carbon lattice in the present invention refers to a six-membered ring formed by carbon atoms, and the doping element A embedded in the carbon lattice will replace the carbon atoms in the original six-membered ring.
[0031] In some specific embodiments of the present invention, based on the total amount of the graphene, the molar content of the doping element A is 0.4-5%. The molar content of the doping element A in the present invention can improve the conductivity and ion wettability of the graphene interface, thereby reducing the impedance of the battery and increasing the rate performance.
[0032] In the present invention, the graphene surface functional groups of the present invention are few and have more excellent electrochemical performance. The graphene is easy to disperse and has a high oil absorption value and a certain rigidity. The battery impedance prepared by using the small-diameter graphene of the scheme is smaller, the low-temperature capacity retention rate is higher, and the cycle stability is better. Among them, the doping element A is embedded in the carbon lattice, which enhances the conductivity and ion wettability of the graphene interface, thereby reducing the impedance of the battery and increasing the rate performance.
[0033] A second aspect of the present invention provides a method for preparing graphene, comprising:
[0034] (1) Under the action of an auxiliary gas, a carbon source gas and an inorganic salt are subjected to a chemical vapor deposition reaction to obtain a salt-encapsulated graphene product;
[0035] (2) subjecting the salt-encapsulated graphene product to ultrasonic cavitation treatment to obtain graphene;
[0036] The thickness of the graphene sheet is 2-6 nm, the diameter of the graphene sheet is 0.2-1 μm, and the oil absorption value of the graphene is 300-800 mL / 100 g.
[0037] Preferably, the chemical vapor deposition reaction is a plasma enhanced chemical vapor deposition reaction.
[0038] In the present invention, the graphene of the present invention is prepared by plasma enhanced chemical vapor deposition reaction. Plasma chemical vapor deposition is a technology in which an auxiliary gas is ionized to form a plasma under the action of an electric field, and a carbon source gas is activated and chemical vapor deposition is realized by plasma discharge. The graphene obtained by plasma enhanced chemical vapor deposition has better crystallinity and conductivity. The plasma enhanced equipment power of the present application is 5kW. By regulating the auxiliary gas (for example, ammonia) in plasma enhanced vapor deposition, or by regulating the inorganic salt (for example, ammonium chloride) in plasma enhanced vapor deposition, a graphene with a molar content of 0.4-5% of N doping is realized, which has more excellent crystallinity and conductivity. And due to the etching effect of the carbon source gas, the obtained graphene has a porous structure, which reduces the obstacle to ion diffusion and increases the liquid absorption of the battery, so that more excellent electrochemical performance can be obtained.
[0039] In the present invention, the graphene obtained by the present invention is obtained by plasma enhanced vapor deposition high temperature reaction to form a lamellae lap support structure, and by controlling the size of the graphene in thickness and sheet diameter, the graphene obtained by the conventional method has a certain rigidity, a stable lamellae lap structure, and thus better prevents the agglomeration of graphene. Therefore, the interaction in the graphene dispersion slurry becomes less and more stable. In addition, due to the small sheet diameter, the construction of the conductive network of graphene and active materials (for example: lithium iron phosphate) will not be affected, and it is easier to be dispersed in the conductive slurry, and other conductive agents can be helped to disperse.
[0040] In some specific embodiments of the present invention, the auxiliary gas is selected from one or more of argon, nitrogen, ammonia, and hydrogen. When the auxiliary gas is selected from ammonia, nitrogen doping can be achieved, thereby improving the comprehensive performance of small-diameter graphene.
[0041] In some specific embodiments of the present invention, preferably, the carbon source gas is selected from CH 4 , C 2 H 2 and C 2 H 4 One or more of the .
[0042] In some specific embodiments of the present invention, the inorganic salt is selected from one or more of potassium sulfate, potassium chloride, sodium chloride and ammonium chloride. The inorganic salt can provide a template for the reaction and promote the growth of graphene. When the inorganic salt is selected from potassium sulfate, sulfur doping can be achieved, thereby improving the conductivity and other comprehensive properties of small-diameter graphene. When the inorganic salt is selected from ammonium chloride, nitrogen doping can be achieved, thereby improving the conductivity and other comprehensive properties of small-diameter graphene.
[0043] In some specific embodiments of the present invention, the flow rate of the auxiliary gas is 1-1000 sccm, the flow rate of the carbon source gas is 1-1000 sccm, the mass of the inorganic salt is 1-2000 g, and the flow rate of the carbon source gas and the mass of the inorganic salt need to be controlled within a reasonable range to ensure the reaction. The main function of the inorganic salt is to provide a template, and only a part of it acts as a doping source to undergo a doping reaction. Therefore, most of the inorganic salt can be condensed and recovered in the subsequent washing solution and reused repeatedly.
[0044] In some specific embodiments of the present invention, the ultrasonic cavitation treatment power is 1000-3000W, and the ultrasonic cavitation treatment time is 1-3h. Among them, ultrasonic cavitation is a high-frequency wave that generates tiny air bubbles in the liquid. The air bubbles expand instantly and can efficiently disperse and peel off the graphene, and form a layer overlap structure. The higher the ultrasonic power and the longer the ultrasonic time, the smaller the graphene sheet diameter.
[0045] In some specific embodiments of the present invention, the plasma enhanced chemical vapor deposition reaction temperature is 800-1200° C., and the plasma chemical vapor deposition reaction time is 1-3 hours. The reaction temperature and reaction time within this range are conducive to the preparation of graphene with appropriate thickness and high crystallinity.
[0046] A third aspect of the present invention provides graphene obtained by the preparation method.
[0047] A fourth aspect of the present invention provides a graphene conductive slurry, wherein the slurry includes the graphene.
[0048] The fifth aspect of the present invention provides an electrode plate, which includes: a current collector and a coating formed by coating the graphene conductive slurry described in the fourth aspect on the current collector. Specifically, the graphene conductive slurry, a binder, an active material and other substances are mixed and coated on the current collector, and the electrode plate is obtained by rolling and drying.
[0049] In some specific embodiments of the present invention, the electrode plate further comprises an active material, and the active material comprises a positive electrode active material or a negative electrode active material. The electrode plate can be a positive electrode plate or a negative electrode plate, preferably a positive electrode plate.
[0050] In some specific embodiments of the present invention, the positive electrode active material is preferably lithium iron phosphate. Preferably, the sheet diameter of the graphene is larger than the D50 particle diameter of the lithium iron phosphate.
[0051] The sixth aspect of the present invention provides a lithium-ion battery, wherein the lithium-ion battery comprises the electrode plate. The electrode plate may be a positive electrode plate or a negative electrode plate. Preferably, the electrode plate is a lithium iron phosphate positive electrode plate.
[0052] A seventh aspect of the present invention provides an electrical device, wherein the electrical device comprises the multiple lithium-ion battery.
[0053] The present invention will be described in detail below through examples.
[0054] The oil absorption value of the present invention is the content of DBP (dibutyl phthalate) absorbed by 100g of graphene, and specific reference is made to GBT 3780.2-2017 Carbon Black Oil Absorption Value Test Method.
[0055] Method for measuring graphene sheet thickness and sheet diameter: the thickness is tested by TEM; the sheet diameter can be tested by SEM, wherein the maximum size of the graphene sheet diameter in different directions measured by SEM is the sheet diameter of the graphene.
[0056] Slurry viscosity test method: The viscosity is tested using a rheometer, which can directly test the viscosity values at different shear rates. The viscosity of the positive electrode slurry is of great significance to the slurry pipeline transportation and positive electrode slurry coating. Low viscosity slurry helps process control and helps to increase the solid content of the positive electrode slurry and improve production line efficiency.
[0057] Positive electrode resistivity test: The two-probe method is used to test the vertical resistivity of the electrode using graphene.
[0058] Rate charge and discharge performance test method: Assemble the electrodes into a soft-pack battery, test the voltage at 2-3.8V, test the capacity at a current density of 0.33-3C, and calculate the capacity retention rate based on the capacity at 0.33C.
[0059] The carbon content of graphene is determined by thermogravimetric testing. The thermogravimetric testing conditions are as follows: the thermogravimetric test is conducted in an air atmosphere, the heating rate is 10°C / min, and the test temperature is 25°C-1000°C.
[0060] XPS spectrum test method: The graphene powder does not need additional treatment, and the prepared graphene powder is directly subjected to X-ray photoelectron spectroscopy test. The test method can refer to the national standard GB / T30544.13-2018.
[0061] In the following examples and comparative examples, if no specific conditions are specified, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. The reagents or instruments used, if no manufacturer is specified, are all conventional products that can be obtained through commercial channels.
[0062] Example 1
[0063] (1) Distribute 20 g of sodium chloride evenly in the sagger and then introduce H 2 and Ar, and heated to 800 °C at a rate of 10 °C / min, followed by CH 4gas, with a gas flow rate of 50 sccm, and react for 2 h to obtain a salt-encapsulated graphene product.
[0064] (2) washing the salt-encapsulated graphene product obtained in step (1) with deionized water to remove salt in the product, subjecting the product to a strong ultrasonic cavitation treatment for 1 h, wherein the ultrasonic cavitation treatment power is 800 W, and then filtering and drying to obtain graphene;
[0065] The graphene has a sheet thickness of 6 nm, a sheet diameter of 1 μm, an oil absorption value of 350 mL / 100 g, contains no doping elements, and has a carbon content of 99.8 wt %.
[0066] Example 2
[0067] (1) Distribute 20 g of sodium chloride evenly in the sagger, then introduce H 2 and Ar, and heated to 800 °C at a rate of 10 °C / min, followed by CH 4 gas, with a gas flow rate of 200 sccm, and react for 2 h to obtain a salt-coated graphene product.
[0068] (2) washing the salt-encapsulated graphene product obtained in step (1) with deionized water to remove salt in the product, subjecting the product to a strong ultrasonic cavitation treatment for 1 h, wherein the ultrasonic cavitation treatment power is 1000 W, and then filtering and drying to obtain graphene;
[0069] The graphene has a sheet thickness of 4 nm, a sheet diameter of 0.8 μm, an oil absorption value of 400 mL / 100 g, contains no doping elements, and has a carbon content of 99.7 wt %.
[0070] Example 3
[0071] (1) Distribute 20 g of potassium chloride evenly in the sagger, then introduce H 2 and Ar, and heated to 950°C at a heating rate of 10°C / min, then C 2 H 2 gas, with a gas flow rate of 350 sccm, and react for 1 h to obtain a salt-coated graphene product.
[0072] (2) washing the salt-coated graphene product obtained in step (1) with deionized water to remove salt in the product, subjecting it to strong ultrasonic cavitation treatment for 2.5 h, wherein the ultrasonic cavitation treatment power is 1200 W, and then filtering and drying to obtain graphene;
[0073] The graphene has a sheet thickness of 3 nm, a sheet diameter of 0.3 μm, an oil absorption value of 450 mL / 100 g, contains no doping elements, and has a carbon content of 99.7 wt %.
[0074] Example 4
[0075] The difference from Example 2 is that CH 4 and NH 3 The gas flow rates are 200 sccm and 20 sccm respectively, and the rest of the steps are the same.
[0076] The graphene has a sheet thickness of 3.8 nm, a sheet diameter of 0.82 μm, and an oil absorption value of 520 mL / 100 g; the graphene contains doped element nitrogen, the molar content of nitrogen is 0.4%, the nitrogen element forms an NC bond with the carbon atoms in the graphene (XPS characterization shows this chemical bond), and the carbon content of the graphene is 99.4 wt%.
[0077] Example 5
[0078] The difference from Example 4 is that CH 4 and NH 3 The gas flow rates were 200 sccm and 60 sccm respectively, and the rest of the steps were the same;
[0079] The graphene sheet thickness is 3.7nm, the sheet diameter is 0.81μm, and the oil absorption value is 580mL / 100g; the graphene contains doped element nitrogen, the molar content of nitrogen is 0.78%, the nitrogen element forms NC bonds with the carbon atoms in the graphene, and the carbon content of the graphene is 99.2wt%.
[0080] Example 6
[0081] The difference from Example 2 is that 20 g of sodium chloride + 5 g of ammonium chloride are evenly distributed in the sagger.
[0082] The rest of the steps are the same;
[0083] The graphene has a sheet thickness of 3.5 nm, a sheet diameter of 0.82 μm, and an oil absorption value of 660 mL / 100 g; the graphene contains doped element nitrogen, the molar content of nitrogen is 0.66%, the nitrogen element forms NC bonds with carbon atoms in the graphene, and the carbon content of the graphene is 99.0 wt%.
[0084] Example 7
[0085] (1) Distribute 20 g of potassium sulfate evenly in the sagger, then introduce H 2 and Ar, and heated to 950°C at a rate of 10°C / min, followed by CH 4 gas, with a gas flow rate of 200 sccm, and react for 2 h to obtain a salt-coated graphene product.
[0086] (2) washing the salt-encapsulated graphene product obtained in step (1) with deionized water to remove the salt in the product, subjecting the product to a strong ultrasonic cavitation treatment for 1 h, wherein the ultrasonic cavitation treatment power is 1000 W, and then filtering and drying to obtain a small-diameter graphene powder;
[0087] The graphene has a sheet thickness of 4 nm, a sheet diameter of 0.83 μm, and an oil absorption value of 750 mL / 100 g; the graphene contains doped elemental sulfur, the molar content of sulfur is 0.5%, the sulfur element forms SC bonds with carbon atoms in the graphene, and the carbon content of the graphene is 98.8 wt%.
[0088] Comparative Example 1
[0089] The flake graphite was intercalated with potassium dichromate and then subjected to a high temperature expansion treatment at 900° C. The obtained expanded graphite was then processed by a sand mill for 6 hours, washed and dried to obtain graphene with a sheet diameter of 5 μm and a sheet thickness of 5 nm, a carbon content of 95.1 wt%, and an oil absorption value of 250 mL / 100 g.
[0090] Comparative Example 2
[0091] The flake graphene was intercalated with hydrogen peroxide and potassium dichromate, and then subjected to a high-temperature expansion treatment at 900° C. The obtained expanded graphite was then treated with a sand mill for 24 hours, washed and dried to obtain graphene with a sheet diameter of 2 μm and a sheet thickness of 2 nm, a carbon content of 93.1 wt%, and an oil absorption value of 240 mL / 100 g.
[0092] Test Case
[0093] (1) The above graphene powder is mixed with a certain amount of PVP dispersant and added to NMP, and double planetary dispersion is performed for 2 hours to obtain a small-diameter graphene conductive slurry, and the solid content of the graphene conductive slurry is 2-5%.
[0094] (2) The above-mentioned graphene conductive slurry is applied to the LFP system to obtain LFP positive electrode slurry (the D50 particle size of the lithium iron phosphate is 800nm), wherein the weight ratio of lithium iron phosphate: conductive agent: PVDF is 100:2.5:2, and the graphene accounts for 1.5 in the conductive agent. The slurry is coated on the current collector, and then the positive electrode sheet is obtained by coating, rolling, slitting, etc.
[0095] (3) A negative electrode slurry is prepared by mixing the negative electrode active material, CMC, SBR and carbon black in a ratio of 100:(1.4-2):(1.8-3):1, coating the negative electrode slurry on the current collector, and then obtaining the negative electrode sheet through coating, rolling and slitting.
[0096] (4) The negative electrode plate separator and the positive electrode plate are stacked in sequence, and then placed in an aluminum plastic film for sealing and drying. After injecting electrolysis, vacuum packaging, aging and capacity separation are performed to obtain a lithium-ion battery.
[0097] Characterization results
[0098] The graphene prepared in Example 1 was characterized, and the scanning electron microscope image is as follows: Figure 1 As shown, the graphene has a sheet-layer overlapping support structure. Due to the formation of such a support structure, the agglomeration problem between graphene layers caused by π-π stacking effect is alleviated.
[0099] The graphene prepared in Example 5 was characterized, and the thermogravimetric spectrum was as follows: Figure 2 As shown, the carbon content of the graphene is 99.2wt%.
[0100] The graphene prepared in Example 7 was characterized by XPS. The XPS spectrum is as follows: Figure 3 As shown, the graphene has SC bonds and has better dispersion ability due to trace heteroatom doping.
[0101] Test example:
[0102] The graphene obtained in Examples 1-7 and Comparative Examples 1-2 were subjected to slurry verification tests. The results of the slurry viscosity test at 0.5% graphene addition under the LFP system are shown in Table 1; then the conductivity of the positive electrode containing the above graphene was tested, and the resistivity of the positive electrode sheet was tested as shown in Table 1; the soft-pack battery was tested for DCIR and rate charge and discharge performance, and the results are shown in Table 1.
[0103] Table 1
[0104] Slurry viscosity / (mPa·s) Positive electrode sheet resistance / (Ω·cm) 3C capacity retention rate / (%) Example 1 2340 84 85 Example 2 2020 76 87.5 Example 3 2310 88 83 Example 4 2203 72 88 Example 5 2203 70 89 Example 6 2126 73 88.4 Example 7 2101 71 88.6 Comparative Example 1 5690 112 80 Comparative Example 2 5210 105 78
[0105] It can be seen from Table 1 that the graphene prepared by the present invention has a smaller sheet diameter, a smaller sheet thickness, and an oil absorption value in a suitable range. The battery prepared by including this graphene has a smaller impedance, a higher low-temperature capacity retention rate, and a better cycle stability. Through Examples 4-7, sulfur or nitrogen is doped in the graphene material, and the doped element is embedded in the carbon lattice, and the electron cloud distribution is further improved by replacing the carbon atoms at the original sites and bonding with multiple surrounding carbon atoms, thereby enhancing the conductivity and ion wettability of the graphene interface, thereby reducing the impedance of the battery and increasing the rate capability. Compared with Examples 1-3, the resistivity of the positive electrode sheet is reduced, and the 3C capacity retention rate is also improved.
[0106] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A graphene, characterized in that: The graphene sheet thickness is 2-6nm, the graphene sheet diameter is 0.2-1μm; and the graphene oil absorption value is 300-800mL / 100g.
2. The graphene according to claim 1, characterized in that The graphene sheet diameter is 0.5-0.85 μm; Preferably, the oil absorption value of the graphene is 500-800 mL / 100 g; Preferably, the carbon content of the graphene is ≥98wt%, preferably ≥99wt%.
3. The graphene according to claim 1 or 2, characterized in that: The graphene further contains a doping element A, and the doping element A is selected from sulfur and / or nitrogen.
4. The graphene according to claim 3, characterized in that The doping element A contained in the graphene forms an AC bond with the carbon element in the graphene sheet; Preferably, the doping element A contained in the graphene is embedded in the carbon lattice of the graphene; Preferably, based on the total amount of the graphene, the molar content of the doping element A is 0.4-5%.
5. A method for preparing graphene, characterized in that: include: (1) Under the action of an auxiliary gas, a carbon source gas and an inorganic salt are subjected to a chemical vapor deposition reaction to obtain a salt-encapsulated graphene product; (2) subjecting the salt-encapsulated graphene product to ultrasonic cavitation treatment to obtain graphene; The thickness of the graphene sheet is 2-6 nm, the diameter of the graphene sheet is 0.2-1 μm, and the oil absorption value of the graphene is 300-800 mL / 100 g.
6. The preparation method according to claim 5, characterized in that: The auxiliary gas is selected from one or more of argon, nitrogen, ammonia and hydrogen; Preferably, the carbon source gas is selected from one or more of CH4, C2H2 and C2H4.
7. The preparation method according to claim 5 or 6, characterized in that: The inorganic salt is selected from one or more of potassium sulfate, potassium chloride, sodium chloride and ammonium chloride.
8. The preparation method according to any one of claims 5 to 7, characterized in that: The flow rate of the auxiliary gas is 1-1000 sccm, the flow rate of the carbon source gas is 1-1000 sccm, and the mass of the inorganic salt is 1-2000 g; Preferably, the ultrasonic cavitation treatment power is 1000-3000W, and the ultrasonic cavitation treatment time is 1-3h; Preferably, the chemical vapor deposition reaction temperature is 800-1200° C., and the plasma chemical vapor deposition reaction time is 1-3 h.
9. Graphene obtained according to the preparation method described in any one of claims 5-8.
10. A graphene conductive slurry, characterized in that: The slurry comprises the graphene described in any one of claims 1-4 and 9.
11. An electrode plate, characterized in that: include: A current collector and a coating layer formed by coating the graphene conductive slurry according to claim 10 on the current collector.
12. The electrode plate according to claim 11, characterized in that: It also includes an active material; the active material is a positive electrode active material or a negative electrode active material; the positive electrode active material is preferably lithium iron phosphate.
13. A lithium ion battery, characterized in that: The lithium-ion battery comprises the electrode plate according to claim 11 or 12.
14. An electrical device, characterized in that: The electrical equipment comprises the lithium-ion battery according to claim 13.